Participatory Governance Driving Innovation in Public Policy Implementation - Jamal Qadar (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study investigates how community participation contributes to public policy innovation through a case study of the People’s School Program and Smart City implementation in Makassar City. Using a qualitative case study approach with 15 key informants, data were collected through interviews, participatory observations, and documentation, then analyzed thematically. The findings show that active community involvement not only enhances policy legitimacy but also drives innovations in public service design, including inclusive education initiatives and more efficient technology-based services. The study concludes that participatory governance serves as a key catalyst for developing adaptive, collaborative, and community-oriented policy transformations, offering both theoretical insights and practical guidance for local governments in designing sustainable innovative policies.